(untitled) (Research, Society and Development, 2022)
Objective: To present an integrative review of the literature on the clinical possibilities of using resin infiltration in minimally invasive dentistry. Methodology: The study was developed through an integrative literature review, carried out between November 2021 and May 2022. Articles published in the electronic databases SCIELO, LILACS and PUBMED were selected, using the following descriptors: resin infiltrant; infiltrating resin; minimally invasive dentistry. Original and literature review articles, published in the last 5 years, available in full, published in Portuguese and English, were included, and books, book chapters, manuals, protocols, guidelines, editorials and other formats of texts that did not pass were not considered. through a rigorous peer review process. Results: After applying the selection criteria, 6 studies were included in this review. The use of resin infiltrant was verified mainly in the treatment of white spot caries lesions, in interproximal regions and in pediatric and adolescent patients. The results found demonstrate that there is a good acceptance of techniques that involve minimal intervention and that in most cases it is possible to observe complete paralysis of the lesions. Conclusion: According to the studies in this review, the clinical possibility of resin infiltration in minimally invasive dentistry is viable and effective in stopping the caries lesion. Furthermore, it is concluded that, compared to other restorative materials and techniques, the resin infiltrant has been shown to be the best alternative for the treatment of non-invasive carious lesions.